Aerobic Rice Production System (ARPS): Improving Productivity and Profitability in Water-Scarce Areas of Bulacan - Dayag, Dinah Marie C.; Soriano , Junel B.; Valdez, Josie A.; Villacorta, Gregory Moses (Annals of Tropical Research, 2014)
On-farm study on rice-based cropping system following recent water-saving technologies for rice production such as ARPS-ARPS, ARPS-alternate wetting and drying (AWD) and existing or Farmers’ Practice (FP) was conducted in a rainfed lowland area in Brgy. Mataas na Parang, San Ildefonso, Bulacan. Field experiments were conducted from June to November 2011 for the wet season and December 2011 to March 2012 for the dry season. Variety used for the ARPS and AWD was NSIc Rc192 and PSB Rc18 for FP. Yield and yield components of the three treatments showed no significant difference during WS. Significant higher number of tillers hill-1 was observed for ARPS-ARPS and ARPS-AWD compared to FP. No significant difference was observed for the yield and yield components during the dry season (DS) for ARPS-ARPS and ARPS-AWD. FP was not established during the DS because of the unavailability of water during the time. During WS, ARPS was the most appropriate cropping system since this intervention obtained higher water productivity and ROI when compared with the FP. During the dry season, AWD and ARPS were suitable to the rainfed lowland areas of Bulacan. Results of this study showed that aerobic rice production system for the rainfed lowland areas improved water and land productivity as well as increased annual rice production and farmers’ income most particularly in ARPS-AWD which consistently gave the highest net income of PhP36,896.20, PhP14,417.50 and PhP51,313.70 during the Wet Season, Dry Season and for the total two cropping seasons, respectively.